2001
DOI: 10.3354/dao044203
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of intracytoplasmic prokaryote infections in Dreissena sp. (Bivalvia: Dreissenidae)

Abstract: This study characterizes intracytoplasmic infections with prokaryote microorganisms in Dreissena sp. (near Dreissena polymorpha) from northeastern Greece and represents the first report of such infections in freshwater bivalves. Light microscope observations of stained tissues revealed basophilic, cytoplasmic inclusion bodies in 87.5% (28/32) of the mussels sectioned. Inclusions in epithelial cells and connective tissues were noted, respectively, in 34.4 and 71.9% of the sample, with 5 mussels (15.6%) having b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…data). Zebra mussels have been reported with rickettisia-like and chlamydia-like infections from Greece (Molloy et al 2001), and a putatively lethal infection of a haplosporidian protozoan was reported in zebra mussels from The Netherlands (Bowmer & Van der Meer 1991, Molloy et al 1997. The relationship, if any, between parasite infections in the zebra mussel and amphipods is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…data). Zebra mussels have been reported with rickettisia-like and chlamydia-like infections from Greece (Molloy et al 2001), and a putatively lethal infection of a haplosporidian protozoan was reported in zebra mussels from The Netherlands (Bowmer & Van der Meer 1991, Molloy et al 1997. The relationship, if any, between parasite infections in the zebra mussel and amphipods is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, investigations of diversity, distribution and significance of endoparasites of D. polymorpha have become important only during the past decade. These studies include Dreissena's mantle-cavity ciliates (Laruelle et al 1999, intracytoplasmic prokaryotes (Molloy et al 2001) and endosymbiont assemblages detected in Dreissena populations in Russia (Kuperman et al 1994, Molloy et al 1996 and Belarus .…”
Section: Introductionmentioning
confidence: 99%
“…A semiquantitative parasite inventory was made by observing 30 to 40 tissue sections per mussel, and parasites were identified following Molloy et al (1997Molloy et al ( , 2001Molloy et al ( , 2005. The level of infection was assessed using standard epidemiological parameters (Bush et al 1997): prevalence (percentage of mussels infected) and mean intensity (mean number of parasites per infected mussel) only for parasites that could be enumerated, i.e.…”
Section: Parasite Identification and Countingmentioning
confidence: 99%
“…and Spheno phrya dreissenae), (2) intracellular bacteria (Rickettsiales-like organisms [RLOs]), and (3) 3 tre ma tode species, Phyllodistomum folium, Bu cepha lus polymor phus and Echinopary phium sp. (Molloy et al 1997(Molloy et al , 2001(Molloy et al , 2005.In the framework of environmental parasitology, a better understanding of interactions between parasite species and host is necessary. However, these interactions are poorly documented in the freshwater zebra mussel, in contrast with other invertebrate species presenting an economic interest.…”
mentioning
confidence: 99%